Stress management for breast cancer survivor in South Sulawesi Province Indonesia - Azriful; Fatmawaty Mallapiang; Nildawati; Syamsul Alam; Rini Jusriani; Masyitha Muis (Elsevier, 2021)
Objective: Cancer is still a health problem serious. Based on the Ministry of Health's report, cancer is the second leading cause of death in the world by 13% after cardiovascular disease. Approximately 30% of cancer patients had adjustment problems and 20% were diagnosed with depression. Methods: A qualitative design with an ethnographic and phenomenological approach with a total of 10 participants. Result: Based on the results of the interview, breast cancer sufferers experience stress and depression when they first find out the diagnosis from the doctor. However, they carry out strategic in order to get rid of excessive anxiety such as reading books, dzikir, meeting fellow survivors, and still trying to sincerely undergo all series of treatments. Conclusion: Support from family, work environment, friends, relatives, fellow breast cancer survivors and treating doctors and fellow survivors greatly contributes to efforts to prevent stress and depression, fellow survivors have communities and groups to provide information and education as well as sharing related to breast cancer.